LEGAL FRAMEWORKS AND HOUSING ENVIRONMENTS IN NORTH CYPRUS - Hoskara, Sebnem Oenal; Cavusoglu, Banu Tevfikler; Ongul, Zehra (Middle East Technical Univ, 2009)
This article aims to explore the effects of laws and regulations on the development of housing environments in North Cyprus, with the aim of opening up some discussions on their future design and planning. Accordingly, the article consists of seven main sections. In the first two, the main and the general concepts of the article are defined, the research field is explained and the problem is specified. In the third section, the issue of housing in North Cyprus, concentrating on its historical development, starting from the British period which is a breaking point on the Island, until 1980s, is presented. In the fourth section, the legal framework, i.e. laws and regulations related to housing is narrated and discussed and in the fifth one, the development of housing after 1980s up-to-date is evaluated mainly by referring the existing legal framework. In the sixth part, some discussion points based on the problems of housing in North Cyprus are set up and finally in the concluding part, some concluding remarks are presented. The methodology followed for the purpose of the research presented in this article is mainly documentary and observative.
Keywords: North Cyprus; housing; mass housing; laws and regulations